HARMONIC ANALYSIS AND MODELLING OF ANNUAL SOIL TEMPERATURE VARIATIONS - LIAKATAS, A. (MAUSAM, 1994)
Harmoni c analysi s using se ries is applied to th e annual variation s of so il tem pe rature From th e surface down to I III depth. TIle fir st harmo nic alon e expla ins about 99% of the variation . II is also shO\\TI th at heat conduction is nor valid in a soil med iuIIIunder exothermic conditions. especially in th e uppermost layer of abom 20 em. as neither the thermal properties. exp ressed by the damping depth (D), nor th e mean soil temperature (nremai n constant with depth . and th e am plitude ofoscilla tio n (.4:) does nOI vary strictly expcnen rially. Thi s is as sumed to be con sider ably reduced soil moisture of thi s in compari son with deeper layers, Finally. cons truction of a mod el to predict mon thly or ten-d ay period mean soil temper atures is based' on wr-at h e r vari ab les (difference between precipitation and pan evaporation), providing an ind ex for the soil moisture de ficit and an est imate of D. and overcomes the difficulties of ch angi ng T and A: with depth.